Antibody therapy for rheumatoid arthritis. - Taylor, P (2003)
High-quality monoclonal antibodies (mAbs) with specificity for relevant disease molecules can now be produced in abundance. Anti-tumour necrosis factor-alpha therapies have set a new standard for symptom control in rheumatoid arthritis, and blockade of tumour necrosis factor has the potential to protect joints from structural damage. Other targets for therapeutic antibodies include the cytokines interleukin (IL)-1, IL-6, IL-8, IL-15, IL-17 and IL-18. In addition, there is preliminary evidence for the clinical efficacy of both keliximab, a mAb targeting the T cell antigen CD4, and rituximab, a chimeric mAb against the B cell antigen CD20 and CTLA4-Ig, which blocks the CD28/B7 interaction. Phase III studies have yet to be undertaken for these novel biological agents, and it is unclear whether any of these agents will have true disease-modifying capabilities.